Unravelling the Dynamics: Determinants Shaping Adoption of Resource Conservation Technologies in Wheat: Adoption Dynamics of Resource Conservation in Wheat - Dey, Anwesha; Sharma, Avdhesh; Gautam, Yash; Singh, H.P. (Journal of Cereal Research, 2025)
The Indo-Gangetic Region characterized as agricultural production hub of India due to the dominance of rice-wheat cropping system. Widespread adoption of Resource Conservation Technologies (RCTs) is driven by multiple factors, to ensure long-term food security and environmental sustainability. The study investigates about determinants influencing adoption of surface seeding technology, zero tillage and rotavator through application of multivariate ordinal logistic regression. Data was collected for different socio-economic factors. The analysis revealed determinants such as farming experience, education, soil type and wheat variety significantly influenced adoption of Surface Seeding Technology. Zero tillage adoption was primarily influenced by soil type and wheat variety factors. Rotavator adoption, however was affected by maximum determinants including landholding size, age, farming experience, education, wheat variety and source of information. These findings highlight the need for data driven policies to promote adoption of RCTs tailored to specific necessities of the farming community.